Postharvest Technology Recent Advances, New Perspectives and Applications - Ahiduzzaman, Md (IntechOpen, 2022)
Postharvest management of food crops is an important part of food safety and security across the supply chain. It includes processing of agricultural produce, storage, packaging and coating, postharvest disease management, extending shelf life, and maintaining food quality and safety. Postharvest Technology - Recent Advances, New Perspectives and Applications discusses some important aspects of postharvest technologies. Chapters address such topics as postharvest preservation technology, postharvest disease management, and postharvest processing and packaging.